Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The question is : Find the general solution of this equation $$ \sin (5\phi)-\sin \phi=\sin (2\phi) $$ I tried to expand $\sin (5\phi)$ and $\sin (2\phi)$, so the equation only contains $\cos\phi$ and $\sin \phi$.

But I can't make it into a form like $\sin(\phi+a)=n$ to get the general solution.

There's another question like this :

Find the general solution of this equation $$ \sin 2x+\sin 4x=\cos 2x+\cos 4x $$

share|cite|improve this question
up vote 3 down vote accepted

Just for your request from avtar:


Now put $n=5$.

share|cite|improve this answer
Thank you for this equation (Haven't learn it before, I'm gonna write it down later:D)I can expand sin5ϕ−sinϕ and get sin(5A) =sin(2A + 3A) = sin(2A)cos(3A) + cos(2A)sin(3A) = 10sin^5(A) - 8 sin^3(A) - 4sin A = 2sin A [ 5sin^4(A) - 4sin^2(A) - 2 ] But still have no idea why sin5ϕ−sinϕ=2cos3ϕsin2ϕ..Could you give some more detail? – Vic. Jun 23 '12 at 13:05
@Vic.: See above second comment. – Babak S. Jun 23 '12 at 13:18

$\sin 5\phi-\sin\phi = 2\cos 3\phi \sin 2\phi$, therefore, equation becomes, $2\cos 3\phi \sin2\phi = \sin 2\phi$ giving possibilities, $\sin2\phi=0$ or $\cos3\phi = 1/2$. For first equation, $2\phi=n\pi \implies \phi=n\pi/2$. For second case, $3\phi = 2n\pi + \pi/3$ or $2n\pi - \pi/3$ giving $\phi = \frac{2n\pi}{3} + \pi/9$ or $\frac{2n\pi}{3} - \pi/9$ . therefore solutions are, $\phi=n\pi/2, \frac{2n\pi}{3} + \pi/9,\frac{2n\pi}{3} - \pi/9$

share|cite|improve this answer
The answer is correct, but I don't know why sin5ϕ−sinϕ=2cos3ϕsin2ϕ. How to get this? – Vic. Jun 23 '12 at 12:45
Vic.: It's trigonometric identity $\sin \alpha - \sin \beta = 2\sin\frac{\alpha-\beta}{2} \cos \frac{\alpha + \beta}{2}$. See Wikipedia – sdcvvc Jun 23 '12 at 13:09
@Vic:you can visit – Aang Jun 23 '12 at 13:10

I think I see a method of solving the second equation. First rewrite the equation as


Now square both sides




This form should be a lot easier to solve, though new roots may have been introduced by squaring both sides.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.